Examining Ordinary Level Secondary Students’ Connections between Classroom-Learned Mathematics with their Real-Life Experiences - Emmanuel Deogratias; Majura Hezron; Thabita Lupeja (Faculty of Tarbiya and Teacher Trainning, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2025)
Mathematics is termed as difficult subject by most of the students in secondary schools and majority of them perform it poorly in their final examinations. This study investigated the extent at which ordinary level secondary students in Tanzania secondary schools connect classroom learned mathematics knowledge with their actual living experiences. The study was constructed in the lens of pragmatism approach of learning which penlights that in education students should be taught things which are practical to the real world and useful in their daily living environment. In this study, 220 ordinary level secondary students were randomly selected as the study sample. Questionnaires were used in data collection. The collected data was analysed through descriptive statistics using statistical graphs and percentages. The study revealed that secondary students in Tanzania rarely connect classroom learned mathematics knowledge with their actual living experiences and most of them failed to explain precisely how learned mathematical topics/knowledge are helpful in their day to day living experiences. The study recommends that classroom learned mathematics should be authentic to student’s real-life experiences.